Improved survival for rectal cancer compared to colon cancer: the four cohort study. Issue 3 (12th September 2016) - Buchwald, Pamela; Hall, Claire; Davidson, Callum; Dixon, Liane; Dobbs, Bruce; Robinson, Bridget; Frizelle, Frank
Abstract : Background: Colorectal cancer (CRC) is the third most common cancer worldwide. This study was undertaken to evaluate survival outcomes and changes of disease outcomes of CRC patients over the last decades. Methods: A retrospective analysis of CRC patients in Christchurch was performed in four patient cohorts at 5 yearly intervals; 1993–94, 1998–99, 2004–05 and 2009. Data on cancer location, stage, surgical and oncological treatment and survival were collected. Univariate, multivariate and Kaplan–Meier survival analysis were performed. Results: There were 1391 patients (355, 317, 419 and 300 per cohort), 1037 colon and 354 rectal cancers, respectively. For colon cancer, right‐sided cancers appeared more common in later cohorts ( P = 0.01). There was a significant decrease in the number of permanent stomas for colon cancer patients ( P = 0.001). There was an analogous trend for rectal cancers ( P = 0.075). More CRC patients with stage IV disease were treated surgically ( P = 0.001) and colon cancer stages I and II tended to have increased survival if operated by a colorectal surgeon ( P = 0.06). Oncology referrals have increased remarkably ( P = 0.001). Overall 56% of patients were alive at 5 years however rectal cancer patients had significantly better 5‐year survival than those with colon cancer ( P < 0.05). Discussion: This four cohort study shows that modern CRC survival continues to improve and is comparable to international standards. Furthermore, rectal cancer patients have a better 5‐year survival than colon cancer patients. The improved survival with early stage colon cancers operated on by specialist colorectal surgeons needs further exploration.